A Randomized Clinical Trial Comparing Chiropractic Adjustments to Muscle Relaxants for Subacute Low Back Pain - Hoiriis, Kathryn T.; Pfleger, Bruce; McDuffie, Frederic C.; Cotsonis, George; Elsangak, Omar; Hinson, Roger; Verzosa, Gregoria T. (Journal of manipulative and physiological therapeutics, 2004)
The adult lifetime incidence for low back pain is 75% to 85% in the United States. Investigating appropriate care has proven difficult, since, in general, acute pain subsides spontaneously and chronic pain is resistant to intervention. Subacute back pain has been rarely studied. To compare the relative efficacy of chiropractic adjustments with muscle relaxants and placebo/sham for subacute low back pain. A randomized, double-blind clinical trial. Subjects (N = 192) experiencing low back pain of 2 to 6 weeks' duration were randomly allocated to 3 groups with interventions applied over 2 weeks. Interventions were either chiropractic adjustments with placebo medicine, muscle relaxants with sham adjustments, or placebo medicine with sham adjustments. Visual Analog Scale for Pain, Oswestry Disability Questionnaire, and Modified Zung Depression Scale were assessed at baseline, 2 weeks, and 4 weeks. Schober's flexibility test, acetaminophen usage, and Global Impression of Severity Scale (GIS), a physician's clinical impression used as a secondary outcome, were assessed at baseline and 2 weeks. Baseline values, except GIS, were similar for all groups. When all subjects completing the protocol were combined (N = 146), the data revealed pain, disability, depression, and GIS decreased significantly ( P < .0001); lumbar flexibility did not change. Statistical differences across groups were seen for pain, a primary outcome, (chiropractic group improved more than control group) and GIS (chiropractic group improved more than other groups). No significant differences were seen for disability, depression, flexibility, or acetaminophen usage across groups. Chiropractic was more beneficial than placebo in reducing pain and more beneficial than either placebo or muscle relaxants in reducing GIS.